Asian development outlook 2004 (New york, 2004)
This is the 2004 edition of Asian Development Oulook , the Asian Development Bank's annual survey of economic progress in its developing member countries in Aisa and the Pacific. First published in 1989, the ADO provides a comprehensive yet concise overview of recent economic developments and current issues. The theme chapter this year will be on Foreign Direct Investment in Asia.
Keywords: Investments